Editorial - Melba Libia Cárdenas (HOW, 2014)
I am pleased to present the first issue of our twenty-first volume. With it we start a new epoch of our journal: the challenge to publish two issues per year so that we can move forward on making our contributors’ works visible more rapidly. This decision has been supported by ASOCOPI’s Board of Directors plus the community present at our 48th annual conference, in October 2013, received this news with enthusiasm.